Pregnancy Weight Gain Limitation by a Supervised Nutritional Program Influences Placental NF-κB/IKK Complex Expression and Oxidative Stress - Hugo Mendieta Zerón (Oman Medical Journal, 2013)
Objective: Nuclear factor kappa B (NF-κB) pathway and oxidative stress participate in endothelial dysfunction, which is one of the causes of pre-eclampsia. Among the human antioxidant mechanisms, there are the enzymes catalase (CAT), glutathione peroxidase (GPx) and superoxide dismutase (SOD). Our aim was to measure NF-κB, its inhibitor (IKK) and oxidative stress in placenta and umbilical cord of pregnant women submitted to a supervised nutritional program.Methods: Two groups were conformed: A) 14 pregnant women with individualized nutritional counseling, and B) 12 pregnant women without nutritional guidance. NF-κB and IKK were assessed by real time PCR (RT-PCR). Enzymatic activity of CAT, GPx, lipoperoxidation (LPO) and SOD were also evaluated.Results: Pregnant women that followed a supervised nutritional program had lower levels of systolic (p=0.03) and diastolic pressure (p=0.043) although they were heavier than the control group (p=0.048). Among all the women, the Spearman correlation was positive between weight gain and placental NF-κB expression (1, p≤0.01). In the placenta, women with nutritional advice had lower enzymatic activity of GPx (p≤0.038) and showed a tendency of IKK to be higher than in women without a nutritional supervised program.Conclusion: A supervised nutritional program in pregnancy offers a proven option to control weight gain, hypertension, NF-κB/IKK complex expression and oxidative stress reactions in the placenta.